Correlation of premature loss and molar relationship of mixed dentition children with a very high def-t index - Widyawati, Hanna; Zenab, Yuliawati; Setiawan, Ame Suciati (Padjadjaran Journal of Dentistry, 2021)
Introduction: Premature loss mainly occurs in mixed dentition periods in their maxillary deciduous and/or mandibular canine, first molar, and/or second molar. The mixed dentition stage occurs in elementary school-aged children, mark with malocclusions and tooth decays, which can be observed from a very high def-t index. This condition will also lead to an abnormal molar relationship. This study was aimed to analyse the correlation of premature loss and molar relationship of mixed dentition children with a very high def-t index. Methods: An analytical observational study with a cross-sectional approach was conducted towards 43 elementary children of Ciawi, Cikeruh 1, and Cikeruh 2 Public Elementary School (SDN), Jatinangor Regency, West Java, Indonesia, aged 7-9 years. The sample was chosen using the purposive sampling method, based on the sample criteria and their willingness to be research subjects. The premature loss of deciduous teeth and primary first molar relationship were observed through extraoral and intraoral examination. The correlation of the premature loss and molar relationship was analysed using Spearman’s rank correlation test. Results: Premature loss significantly affected the permanent first molars relationship in children with no succedaneous teeth (p=0.02, p<0.05), however, it was showed no significant effect in children with succedaneous teeth (p=0.07, p>0.05). The Spearman’s rank correlation test results showed a positive correlation between premature loss and molar relationship of mixed dentition children with a very high def-t index. Conclusion: Premature loss significantly affected the permanent first molars relationship in children with no succedaneous teeth. However, it was showed no significant effect in children with succedaneous teeth. A positive correlation is found between premature loss and molar relationship of mixed dentition children with a very high def-t index. The higher the premature loss, the more abnormal molar relationship will be found in mixed dentition children with a very high def-t index.